1966
DOI: 10.1042/bj0990123
|View full text |Cite
|
Sign up to set email alerts
|

The structure of bactoprenol, a lipid formed by lactobacilli from mevalonic acid

Abstract: 1. The name ;bactoprenol' has been given to the most abundant lipid formed by three species of lactobacilli from mevalonic acid. 2. A method for the preparation of pure bactoprenol is described. 3. The thin-layer chromatographic properties of bactoprenol and of its acetylated and hydrogenated derivatives resembled those of dolichol. 4. Analysis by mass spectrometry and by nuclear magnetic resonance showed that the molecule is formed by condensation of 10 unsaturated isoprene units and 1 saturated isoprene unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

1972
1972
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 9 publications
0
40
0
1
Order By: Relevance
“…While the genome of B. subtilis revealed genes encoding enzymes of the GAP-pyruvate pathway for IPP biosynthesis, other gram-positive bacteria, including Lactobacillus plantarum (49), Staphylococcus aureus (18,33), Staphylococcus carnosus (21), and Streptococcus mutans (50), incorporate radiolabeled mevalonate into isoprenoids, suggesting that these bacteria use the mevalonate pathway for the synthesis of IPP. Furthermore, Doolittle and Lodgson (15) and Bochar et al (7) reported the presence of the HMG-CoA reductase gene in the genomes of Streptococcus pneumoniae and Streptococcus pyogenes.…”
mentioning
confidence: 99%
“…While the genome of B. subtilis revealed genes encoding enzymes of the GAP-pyruvate pathway for IPP biosynthesis, other gram-positive bacteria, including Lactobacillus plantarum (49), Staphylococcus aureus (18,33), Staphylococcus carnosus (21), and Streptococcus mutans (50), incorporate radiolabeled mevalonate into isoprenoids, suggesting that these bacteria use the mevalonate pathway for the synthesis of IPP. Furthermore, Doolittle and Lodgson (15) and Bochar et al (7) reported the presence of the HMG-CoA reductase gene in the genomes of Streptococcus pneumoniae and Streptococcus pyogenes.…”
mentioning
confidence: 99%
“…Similar amounts of free isoprenoid-alcohol and the derived non-functional fatty acyl ester were found in Streptococcus faecalis [3]. Myxococc~s filvus (Kleinig, H., personal communication), Lactobacillus plantantm [4,5] and in Listeria monocytogenes [6]. A preponderance of the pools of non-functional free isoprenoidalcohol and its fatty acyl ester has also been found in yeast, plant and mammalian species [7] .…”
Section: Introductionmentioning
confidence: 93%
“…Bactoprenol is synthesized by lactobacilli from [14C]mevalonic acid (Thorne & Kodicek, 1962b;1966). For its determination bacterial fractions were saponified, and the unsaponifiable lipids were extracted and chromatographed on thin layers of silica gel G with 10 % (v/v) ethyl acetate in n-heptane.…”
Section: Methodsmentioning
confidence: 99%
“…Bactoprenol, a C, isoprenoid alcohol synthesized from mevalonic acid (Thorne & Kodicek, 1966), is located in the mesosomes (Thorne & Barker, 1969) and the plasma membrane (Barker & Thorne, 1970) of lactobacilli. Reappraisal of its mass spectrum shows that it does not, as originally believed, contain any saturated residues.…”
Section: Introductionmentioning
confidence: 99%